Digital Humanities and Digital Skills in the Future of Work - Krzysztof Wasilewski (Peter Lang GmbH, Internationaler Verlag der Wissenschaften, 2025)
The volume covers the field of digital humanities regarding the future of work. What digital skills will be needed in the nearby future? How digitization and digitalization change the very nature of science and the workplace? The authors represent higher education institutions which form the EU4Dual European University, as well as associated Ukrainian universities. Therefore the papers are often a result of applied and cooperative research, done together with the industry. As such they focus on practical usage of digital humanities and digital skills.